2019
DOI: 10.1037/pas0000723
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the psychometric properties of the Suicide Stroop Task.

Abstract: Behavioral measures are increasingly used to assess suicidal thoughts and behaviors. Some measures, such as the Suicide Stroop task, have yielded mixed findings in the literature. An understudied feature of these behavioral measures has been their psychometric properties, which may affect the probability of detecting significant effects and reproducibility. In the largest investigation of its kind, we tested the internal consistency and concurrent validity of the Suicide Stroop Task, drawing from seven separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 65 publications
2
26
1
Order By: Relevance
“…Thus, it may be that attentional control when presented with emotional stimuli may be more sensitive to emotional states. Such deficits have been reported in some previous studies (Cha et al, 2010;Chung & Jeglic, 2016;Williams & Broadbent, 1986), but not others (Richard-Devantoy et al, 2016;Wilson et al, 2019). Still, current results did not point to recency effects for attentional control when presented with suicide cues.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Thus, it may be that attentional control when presented with emotional stimuli may be more sensitive to emotional states. Such deficits have been reported in some previous studies (Cha et al, 2010;Chung & Jeglic, 2016;Williams & Broadbent, 1986), but not others (Richard-Devantoy et al, 2016;Wilson et al, 2019). Still, current results did not point to recency effects for attentional control when presented with suicide cues.…”
Section: Discussioncontrasting
confidence: 54%
“…This deficit has also been demonstrated prospectively (Cha et al, 2010). However, others have not replicated findings with this task (Richard-Devantoy et al, 2016;Wilson et al, 2019). Still, this overall body of literature points to several neurocognitive domains that are impaired in individuals who attempt suicide, along with possible differences in processing suicide-related cues.…”
Section: Introductionmentioning
confidence: 93%
“…The clinical and non-clinical population investigated in this study did not show significant attentional bias in the suicide Stroop; hence, it seems that the incidence of attentional bias towards suicide-related information is not related to clinical conditions. Chung and Jaglic (2016), Richard-Devantoy et al (2016) and Wilson et al (2019), reported no significant difference between the reaction times of neutral, positive emotional, negative emotional, and suicide Stroop tests [9][10][11] which is consistent with the findings of the present study. However, Becker et al (1999) and William and Bordbent (1986) reported that the reaction time of suicide Stroop in suicide attempters was significantly longer than that of other types of Stroop tests [12,13].…”
Section: Discussionsupporting
confidence: 91%
“…Several indirect methods have been introduced, which were used to predict suicidal behaviors and evaluate suicidal risk. These methods include the Kesler's 10-item syndrome checklist (k-10), formal analysis of the suicidal situation (Hamedi, Colborn, Bell, Chalker, & Jobes, 2019), Eye-Blink/Startle Response Paradigm (Goodman & Hazlett, 2015), thermography technique to record auto-physiological responses, such as the opening of sweat pores while answering to the questions regarding the suicide (Familoni et al, 2012), Implicit Association Test (Nock et al, 2010) and Suicide Stroop Task (SST) (Chung & Jeglic, 2016;Richard-Devantoy, Ding, Turecki & Jollant, 2016;Wilson et al, 2019;Becker, Strohbach & Rinck, 1999;Williams & Broadbent, 1986;Cha, Najmi, Park, Finn & Nock, 2010;Stewart et al, 2017). Some of these methods, such as the SST, focus on "Attentional Bias" in case of suicide information processing.…”
Section: Introductionmentioning
confidence: 99%
“…The person is asked to recognize the color of the words without considering their meanings. In case of attention bias towards suicide-related words, the individual is not able to complete the cognitive task as soon as possible and this delay in responding to the task, which is the result of the cognitive interference, is deemed as the attention bias to those suicide-related stimuli (Wilson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%